Performance of post-mortem diagnostic tests for tuberculosis in wild ungulates at low and high prevalence assessed using Bayesian latent class models - Cardoso, Beatriz; Jiménez-Ruiz, Saúl; Perelló Jiménez, Alberto; Nóvoa, Miguel; Santos, João P. V.; Correia-Neves, Margarida; Gortázar, Christian; Santos, Nuno (Frontiers in Veterinary Science, 2024)
Animal tuberculosis (TB) is often maintained by multi-host communities, including livestock and wildlife. Quantitative studies of such communities require estimating the true prevalence of TB, correcting the apparent prevalence by the diagnostic sensitivity (Se) and specificity (Sp) of the test. The goal of this study was to lay the foundations for estimating the true prevalence of TB in wild ungulate populations (wild boar and two cervids: red deer and fallow deer). We used Bayesian latent class models to assess the Se and Sp of gross pathology, IS6110 real-time PCR in tissues, bacteriological culture, and P22 indirect ELISA. We analyzed 308 harvested wild ungulates (211 wild boar and 97 cervids: 92 red deer and 5 fallow deer). The Se of bacteriological culture (80.4%, CI95 61.0–96.3%) and gross pathology (87.9%, CI95 69.5–99.9%) was reasonably good in wild boar. These tests showed lower Se in cervids: 60.2% (CI95 38.3–82.3%) for bacteriological culture and 81.5% (CI95 63.6–96.2%) for gross pathology. The Se of the real-time PCR was low (50.7% in wild boar and 53.0% in cervids). These tests showed Sp between 95.2 and 99.1% in both taxa. The P22 ELISA performed reasonably well in wild boar (Se = 71.9%, CI95 59.2–83.4%; Sp = 98.8%, CI95 96.9–99.9%) but lacked Sp in cervids (Se = 77.1%, CI95 62.9–89.7%; Sp = 74.5%, CI95 65.7–83.3%). The real-time PCR in wild boar and cervids and bacteriological culture in cervids tended to show higher Se in low-prevalence populations, possibly due to a higher proportion of early-stage TB lesions. In cervids, the parallel interpretation of gross pathology and bacteriological culture significantly improved the diagnostic performance (Se = 93.1%, CI95 84.7–98.9%; Sp = 92.9%, CI95 86.0–98.3%). Our results allow the estimation of true prevalence from the results of a single diagnostic test applied to harvested wild boar, red deer, and fallow deer, paving the way for more precise quantitative ecological studies of the multi-host TB maintenance community.